Avaliação de créditos de carbono na fase agrícola do setor sucroalcooleiro: um estudo de caso na Paraíba - Vilar, Bruno Lopes (2013)
The growing use of fossil fuels has resulted in increased greenhouse gas emissions, generating the "Greenhouse Effect" that contribute to global warming. In 1997, several world leaders signed the "Kyoto Protocol" which foresaw a reduction of about 5.2% in the levels of greenhouse gas emissions in 1990. Among various advances made, there is the Clean Development Mechanism (CDM), which proposes that developed countries that are unwilling or unable to reduce their emissions can buy from other countries known titles as "Carbon Credits", setting up a new market for the countries of the treaty grantors. In this scenario, the ethanol industry stands out among the rest of the energy sector due to its production matrix is grounded in a bioenergy source that is sugar cane. This sector is distributed throughout Brazil. However, in the northeastern states, especially in Paraíba mainly operates more consistently in the economy, due to its character plaintiff in volume of labor and its location near major cities. The aim of this study was to describe how is the agricultural phase in Monte Alegre mill / PB, describing the possibilities for projects in Carbon Credits that can be developed at this stage of the productive sector and monetise the generation of these credits within the revenue structure of plant. Through the method of production function, one can measure the economic potential generator of credits, from literature surveys, interviews and analysis of the production process employed. The results indicate a great potential monetary contribution from the sale of carbon credits, contributing to the reduction of greenhouse gases as well as expanding the possibilities of revenue for the sugar industry.